Congenital Malaria - Eisa, El Fadil; Mirghani, Omer Ahmed (Gezira Journal of Health Sciences, 2004)
This research is under processing, Still we are collecting data and cases. Introduction and Literature Review .Congenital malaria is defined as the presence of malaria parasites in the RBC of the newborn less than 7 days old (1). Symptoms and signs of  congenital malaria include: Fever,   RDS , pallor,  GIT upset, jaundice and hepatosplenomegally.